Open source solutions for small business problems - John Locke (Charles River Media, 2004)
Systems requirements for accompanying computer disk: Windows 98, Windows 2000, or later. Most appplications will work in Windows NT 4.0.; Pentium 233 MHz (Recommended 500 MHz or greater); At least 64 MB of RAM; About 500 MB of hard drive space to install everything; some programs can be installed with less than 1 MB of drive space